PERKEMBANGAN PERKERETAAPIAN PADA MASA KOLONIAL DI SEMARANG TAHUN 1867-1901 - Ratnawati, Yusi (Journal of Indonesian History, 2014)
Semarang chosen as the initial construction of railroads because the city has an important role for government Kolonila Netherlands. In addition to administration as the city of Semarang also serve as a center of trade, especially sugar at that time became the main commodity. The development of railways in Semarang very rapidly even to say Semarang is a center for the development of railways. There are at least six stations in the city of Semarang is Kemijen station, station Jurnatan, Jomblang station, Pendikran stations, stations and station Tawang Poncol. Based on the research that has been done can be obtained information that (1) the history of railways in Indonesia began with the construction of a rail network that connects between Semarang-Vorstenlanden under the supervision of NISM. Construction of the railroad network continues to spread throughout the islands of Java and outside Java. Implementation of development carried out by the SS and SSS which is owned by the Government. (2) The development of transport, railways in Semarang started with the construction of a railway between Semarang (Kemijen) and responsibilities. In 1900 the railway industry in Hyderabad is increasing with the presence of several private companies that build roads tram. (3) The role perkretaapian in Semarang accelerate the mobility of people in the city of Semarang. This is because the increase in plantation crops and agriculture encourages the Government of the Netherlands East Indies add ground transportation that can penetrate into the interior regions of Central Java at a cost that is cheaper, faster to transport the plantation and agriculture in a large capacity so the government built a railroad. Â